IgG4-related disease: current challenges and future prospects - Lang D; Zwerina J; Pieringer H (Dove Medical Press, 2016)
David Lang,1 Jochen Zwerina,2 Herwig Pieringer1,3 1Second Department of Internal Medicine, Kepler University Clinic, Linz, 2First Department of Internal Medicine, Ludwig Boltzmann-Institute of Osteology, Hanusch Hospital, Vienna, 3Paracelsus Private Medical University, Salzburg, Austria Abstract: Immunoglobulin G4-related disease (IgG4-RD) represents an immune-mediated fibroinflammatory condition with a characteristic histopathological appearance that can affect various organs. Although numerous single-organ manifestations have been described more than a century ago, its systemic nature and unique features were only discovered in the last 2 decades, when IgG4-RD emerged as a new entity of disease. IgG4-RD is usually considered a rare disease, but its true epidemiology has not yet been fully clarified. Also, despite recent advances in the identification of the underlying immunological processes, its pathophysiology is only incompletely understood till now. The diagnostic workup of IgG4-RD is complex and usually requires a combination of clinical examination, imaging, histological, and serological analyses. However, no finding alone is specific for IgG4-RD. Therefore, its diagnosis requires careful interpretation of examination results in context with the patient’s clinical appearance as well as the exclusion of a broad variety of differential diagnoses. The past years brought rapid advances concerning this novel disease entity: diagnostic criteria, further insights into the underlying immunological processes, new biomarkers, and novel therapeutic approaches were proposed and widened the knowledge in the field of IgG4-RD. Still, a greater number of questions remain unanswered, and many recent developments require further discussion and proof from clinical trials. This review should give an overview on current knowledge and future perspectives in epidemiology, pathophysiology, diagnosis, and therapy of IgG4-RD. Keywords: PET/CT, autoimmune pancreatitis, plasmablast, rituximab